2009
DOI: 10.1111/j.1462-2920.2009.01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structure and composition of bacterial communities from temperate and tropical freshwater ecosystems

Abstract: We used a partial 16S rRNA sequencing approach to compare the structure and composition of the bacterial communities in three large, deep subalpine lakes in France with those of communities in six shallow tropical reservoirs in Burkina Faso. Despite the very different characteristics of these ecosystems, we found that their bacterial communities share the same composition in regard to the relative proportions of the different phyla, suggesting that freshwater environmental conditions lead to convergence in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 60 publications
8
76
0
2
Order By: Relevance
“…The freshwater Actinobacteria are also present in the bottom waters (hypolimnion) of lakes (20), but their abundance often decreases with decreasing oxygen concentrations (3,205). This high level of abundance in the epilimnion has proven to be consistent across lake types, as the Actinobacteria are common among oligotrophic (101), mesotrophic (39,101,237), eutrophic (233), and dystrophic (141) lakes. Likewise, the dominance of the Actinobacteria is spread across the globe.…”
Section: Phylum Actinobacteriamentioning
confidence: 96%
See 2 more Smart Citations
“…The freshwater Actinobacteria are also present in the bottom waters (hypolimnion) of lakes (20), but their abundance often decreases with decreasing oxygen concentrations (3,205). This high level of abundance in the epilimnion has proven to be consistent across lake types, as the Actinobacteria are common among oligotrophic (101), mesotrophic (39,101,237), eutrophic (233), and dystrophic (141) lakes. Likewise, the dominance of the Actinobacteria is spread across the globe.…”
Section: Phylum Actinobacteriamentioning
confidence: 96%
“…1 , manuscript in press at Environmental Microbiology (141a) (includes GenBank accession numbers FJ827781 to FJ828505); 2 , GenBank accession numbers for the sequenced clones are HQ386253 to HQ386631; 3 , GenBank accession numbers for the sequenced clones are FJ916807 to FJ916903 and HQ530565 to HQ532908, except HQ530583, HQ531638, and HQ532521. (Based on data from references 2, 3,4,11,20,22,24,27,35,38,41,42,44,45,46,48,49,52,61,63,69,73,74,82,83,84,85,89,93,95,101,105,106,108,116,124,126,127,134,135,139,140,141,147,148,149,15...…”
Section: Creating a Modern View Of Freshwater Lake Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the acI lineage within the phylum Actinobacteria are an intriguing group of free-living ultramicrobacteria that dominate many freshwater ecosystems (Newton et al, 2011), including highnutrient eutrophic (Wu et al, 2007), low-nutrient oligotrophic (Humbert et al, 2009) and dystrophic lakes (Newton et al, 2006). They are also abundant in some marine estuaries (Glockner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear if even deeper sequencing would have revealed the few common taxa seen in the global data set (Newton et al 2011) that were not detected in the Québec lakes. Much smaller data sets from temperate and tropical ecosystems also provided hints that freshwater lakes include a core set of common taxa (Humbert et al 2009). Other studies from circumpolar freshwaters indicated that the same common bacterial taxa can be identified throughout the pan-Arctic region (Crump et al 2009).…”
Section: Discussionmentioning
confidence: 99%